A new approach to optimal control of nonlinear vehicle suspension system with input constraint. (August 2018) - Abdi, Bahman; Mirzaei, Mehdi; Mojed Gharamaleki, Reza
The vehicle active suspension system is a multi-objective control system with the input constraint. In this paper, a new effective method is proposed for constrained optimal control of a vehicle suspension system including nonlinear characteristics for elasto-damping elements. In the proposed method, an equivalent constrained optimization problem is firstly formulated by performing a performance index which is defined as a weighted combination of predicted responses of nonlinear suspension system and control signal. Then, the constrained optimization problem is analytically solved by the Kerush–Kuhn–Tucker (KKT) theorem to find the control law. The proposed constrained controller is compared with the unconstrained optimal controller for which the limitation of control force is satisfied by regulation of its weighting factor in the performance index. Simulation studies are conducted to show the effectiveness of two controllers. The results indicate that the constrained controller utilizes the maximum capacity of external forces and consequently attains a better performance in the presence of force limitations.